Comovements in the equity prices of large complex financial institutions - Hawkesby, Christian; Marsh, Ian W.; Stevens, Ibrahim (Journal of Financial Stability, 2007)
In recent years, mergers, acquisitions and organic growth have meant that some of the largest and most complex financial groups have come to transcend national boundaries and traditionally defined business-lines. As a result, they have become a potential channel for the cross-border and cross-market transmission of financial shocks. This paper analyses the degree of comovement in the equity prices of a selected group of large complex financial institutions (LCFIs), and assesses the extent to which movements are driven by common factors. A relatively high degree of commonality is found for most LCFIs although there are still noticeable divisions between sub-groups of LCFIs, both according to geography and to a lesser extent primary business-line.